2020
DOI: 10.3389/fpls.2020.01065
|View full text |Cite
|
Sign up to set email alerts
|

Interplay Between Silicon and Iron Signaling Pathways to Regulate Silicon Transporter Lsi1 Expression in Rice

Abstract: Silicon (Si) is not an essential element, but it is a beneficial element for growth and development of many plant species. Nevertheless, how plants regulate the initial uptake of silicon (Si) remains poorly understood. It has been proposed that the regulation of Si uptake is largely regulated by Si availability. However, the current model is clearly reductionist and does not consider the availability of essential micro-elements such as iron (Fe). Therefore, the present study investigates the regulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Exudation of organic ligands (mainly PSs) by roots of Fe deficient barley plants can indirectly increase Si availability in the rhizosphere ( Gattullo et al, 2016 ), as a consequence of nutrient (e.g., Fe) mobilization from silicate minerals by liberation of silicic acid. In rice roots, low supply of both N and Fe led to up-regulation of OsLsi1 ( Wu et al, 2017 ; Chaiwong et al, 2020 ) and OsLsi2 ( Wu et al, 2017 ). A similar effect was observed in K-deficient barley, where up-regulation of HvLsi1 , HvLsi2 and HvLsi6 was responsible for accumulation of Si in the shoot ( Hosseini et al, 2017 ).…”
Section: Essential and Beneficial Element Status Affects Silicon Uptake And Distributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exudation of organic ligands (mainly PSs) by roots of Fe deficient barley plants can indirectly increase Si availability in the rhizosphere ( Gattullo et al, 2016 ), as a consequence of nutrient (e.g., Fe) mobilization from silicate minerals by liberation of silicic acid. In rice roots, low supply of both N and Fe led to up-regulation of OsLsi1 ( Wu et al, 2017 ; Chaiwong et al, 2020 ) and OsLsi2 ( Wu et al, 2017 ). A similar effect was observed in K-deficient barley, where up-regulation of HvLsi1 , HvLsi2 and HvLsi6 was responsible for accumulation of Si in the shoot ( Hosseini et al, 2017 ).…”
Section: Essential and Beneficial Element Status Affects Silicon Uptake And Distributionmentioning
confidence: 99%
“…Increasing evidence suggests that nutritional status can affect Si accumulation and distribution in plants (e.g., Kim et al, 2014 ; Bokor et al, 2015 ; Hosseini et al, 2017 ; Wu et al, 2017 ; Chaiwong et al, 2020 ; Minden et al, 2020 ; Xiao et al, 2021 ). However, only a few studies have investigated the effect of specific nutrient imbalances on the expression of Si transporters and could be additionally affected by the Si concentration in the shoot ( Mitani-Ueno and Ma, 2020 ).…”
Section: Essential and Beneficial Element Status Affects Silicon Uptake And Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the Lsi1 gene in rice is downregulated by Si supply, dehydration stress and abscisic acid (more strongly in Si-depleted plants), suggesting regulation of active Si uptake in response to changes in the transpiration stream and plant internal water balance [ 123 ]. Further studies have demonstrated how the expression of Lsi1 , Lsi2 and Lsi6 genes is regulated by plant hormones [ 124 ] and internal Si and metal concentrations [ 125 , 126 ].…”
Section: Silicon Uptake By Plantsmentioning
confidence: 99%
“…A wealth of information has been generated during the last two decades on morphological and physiological adaptations of plants in response to the changes in the availability of mineral nutrients ( Gniazdowska and Rychter, 2000 ; Maathuis, 2009 ; Krouk et al, 2011 ; Gruber et al, 2013 ; Zhao and Wu, 2017 ; Krouk and Kiba, 2020 ). Protein-coding genes involved in the uptake, mobilization, storage, and assimilation of macro/micro-elements have been characterized to some extent; and regulatory networks affecting their expression in response to the changing nutritional status are being elucidated ( Schachtman and Shin, 2007 ; Giehl et al, 2009 ; Gojon et al, 2009 ; Liu et al, 2009 ; Pilon et al, 2009 ; Hindt and Guerinot, 2012 ; Vigani et al, 2013 ; Briat et al, 2015 ; Chaiwong et al, 2020 ). Crop plants are frequently subjected to nutrients imbalance which adversely affects several metabolic processes.…”
Section: Introductionmentioning
confidence: 99%